Clinkering and hydration of belite-alite-ye´elimite cement. (July 2017) - Londono-Zuluaga, D.; Tobón, J.I.; Aranda, M.A.G.; Santacruz, I.; De la Torre, A.G.
Abstract: Some belite-ye´ elimite-ferrite (BYF) cements present low mechanical strengths mainly due to the slow reactivity of belite. A solution to this problem may be the activation of BYF clinkers by preparing them with a coexistence of alite and ye'elimite, which are known as belite-alite-ye´ elimite (BAY) cements. The objective of this work was the preparation of BAY mortars that show higher mechanical strengths than BYF mortars. In order to attain this, the clinkering conditions to prepare BAY-clinker (2 kg) with the following mineralogical composition 60.6 (2) wt% of belite, 14.3 (2) wt% of alite and 10.4 (1) wt% of ye'elimite were optimized (900°C/30 min-1300°C/15 min). The hydration mechanism of cement pastes (with 12 wt% of anhydrite and water-to-cement ratios of 0.4 and 0.5) was studied through laboratory X-ray powder diffraction and thermo-analyses. Finally, BAY mortars with higher compressive strengths than BYF-mortars were obtained (viz. 24.8 and 17.1 MPa for BAY and BYF mortars at 7 days of hydration, respectively).